Effective treatment protocol for poor ovarian response: A systematic review and meta-analysis - Yadava Bapurao Jeve; Harish Malappa Bhandari (Wolters Kluwer Medknow Publications, 2016)
Poor ovarian response represents an increasingly common problem. This systematic review was aimed to identify the most effective treatment protocol for poor response. We searched MEDLINE, EMBASE, and The Cochrane Library from 1980 to October 2015. Study quality assessment and meta-analyses were performed according to the Cochrane recommendations. We found 61 trials including 4997 cycles employing 10 management strategies. Most common strategy was the use of gonadotropin-releasing hormone antagonist (GnRHant), and was compared with GnRH agonist protocol (17 trials; n = 1696) for pituitary down-regulation which showed no significant difference in the outcome. Luteinizing hormone supplementation (eight trials, n = 847) showed no difference in the outcome. Growth hormone supplementation (seven trials; n = 251) showed significant improvement in clinical pregnancy rate (CPR) and live birth rate (LBR) with an odds ratio (OR) of 2.13 (95% CI 1.06-4.28) and 2.96 (95% CI 1.17-7.52). Testosterone supplementation (three trials; n = 225) significantly improved CPR (OR 2.4; 95% CI 1.16-5.04) and LBR (OR 2.18; 95% CI 1.01-4.68). Aromatase inhibitors (four trials; n = 223) and dehydroepiandrosterone supplementation (two trials; n = 57) had no effect on outcome.